2019
DOI: 10.3892/ol.2019.10527
|View full text |Cite
|
Sign up to set email alerts
|

Systematic re‑analysis strategy of serum indices identifies alkaline phosphatase as a potential predictive factor for cervical cancer

Abstract: The aim of the present study was to identify predictive factors for cervical cancer (CC) progression using a multistage approach. The present study obtained data from 390 healthy women and 259 patients with cervical cancer between June 2012 and June 2017, and used a multiple stage re-analysis strategy for clinical detection of CC. A total of seven types of serum indices were used in the present study, including sugar chain antigen 125 (CA-125), sugar chain antigen 199 (CA-199), α fetoprotein (AFP), carcino- em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…40 Moreover, a recent published article found that high levels of ALP could influence tumorigenesis and predict outcomes in cervical cancer patients. 41 In our present study, the AUC of AAPR was similar to that of ALB and ALP. However, AAPR has several advantages in cervical cancer patients compared with the other two indices.…”
Section: Discussionsupporting
confidence: 81%
“…40 Moreover, a recent published article found that high levels of ALP could influence tumorigenesis and predict outcomes in cervical cancer patients. 41 In our present study, the AUC of AAPR was similar to that of ALB and ALP. However, AAPR has several advantages in cervical cancer patients compared with the other two indices.…”
Section: Discussionsupporting
confidence: 81%
“…However, the speci c mechanism of the above-mentioned indicators as predictors of LNM in CC patients is unclear, and further studies are warranted. Furthermore, it has been suggested that some hematological parameters that were not used in this study, such as sugar chain antigen 125 (CA125), sugar chain antigen 199 (CA19-9), α fetoprotein (AFP), and alkaline phosphatase (ALP), may also be associated with LNM in CC patients, which may also provide a feasible direction for future research [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that cervical cancer is also closely related to the marker CA125 and CA199. It has been reported [ 42 44 ] that the carbohydrate antigens CA125 and CA199 are expressed at high levels in a variety of malignancies. In this study, the levels of CA125 and CA199 in patients with adenocarcinoma were significantly higher than those in patients with squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%